Using low sulfate seawater during water injection to avoid scaling problem - Md. Yassin, A. A.; Ghazali, M. N. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
A study was carried to see the effect of low sulfate seawater as water injector to avoid scaling problem. In this study, low sulfate seawater was used. Solubility test and permeability test have been conducted to show the effect of low sulfate seawater. For solubility test, six jars contain formation water were used. Seawater and low sulfate seawater (75%, 50%, 25% and 1% sulfate reduction) were added into the jars respectively. The ratio of seawater and formation water in the jar is 50:50. The solubility of sulfate was compared between seawater and five types of low sulfate seawater. For permeability test, six cores contain formation water were used as medium injector. Seawater and five type of low sulfate seawater (75%, 50%, 25%, 5% and 1% sulfate reduction) were injected into the six cores which length 1 in after the experiment to get the mass of~recipitation. The significant of temperatures also were considered in this study are 30 C, 50°C and 70°C. Result from the solubility test showed that precipitation occurred in all jars containing seawater and in the low sulfate content seawater but the amount of precipitation was reduced. For the permeability test, it's shown that the mass of precipitation decreased when the low sulfate content was used. The effect of temperature showed that the mass of precipitation decreased when temperatures is increased. It can be concluded that even the sulfate content were reduced to 1% sulfate reduction there may still be a scaling potential and squeeze treatments may still be required.